Fast Earth Fault Location by Analysing the Character of the Initial Processes - Gudzius, S.; Karaliute, U.; Markevicius, L. A.; Morkvenas, A.; Miliune, R. (Elektronika ir Elektrotechnika, 2011)
Nowadays it is thought that distribution power networks have the ability to isolate damaged power network place by making optimal links, to identify the fault character, to recognize the character of transients, to establish the fault cause and estimate the state of electrical equipment. For such an objective, fast identification of the earth fault and its place location is a very important problem which requires reliable solutions. The paper describes the new algorithm of earth fault detection and location which is based on the analysis of the initial processes of the fault and its keystone elements. The earth fault detection and location algorithm has been implemented in distribution network state identification terminals. Ill. 6, bibl. 11 (in English; abstracts in English and Lithuanian). http://dx.doi.org/10.5755/j01.eee.111.5.356